Ionospheric Scale Index Map Based on TEC Data for Space Weather Studies and Applications - C. M. Denardini; G. A. S. Picanço; P. F. Barbosa Neto; P. A. B. Nogueira; C. S. Carmo; L. C. A. Resende; J. Moro; S. S. Chen; E. Romero‐Hernandez; R. P. Silva; A. V. Bilibio (Space Weather)
Abstract The present work shows the preliminary results from the analysis for developing an ionospheric scale index map based on the Disturbance Ionosphere indeX (DIX). This index aims to target all the different user groups affected by ionospheric disturbances, for example, the navigation, positioning, and satellite communication users, in a simple and straightforward approach. Therefore, we used the vertical total electron content (VTEC) over South America to calculate the total electron content (TEC) maps covering latitudes from 60°S to 20°N and longitudes from 90°W to 30°W, with 0.5° × 0.5° resolution. Afterward, the DIX maps are obtained to reveal the variation of the TEC over an average quiet ionosphere background. In order to illustrate the use of the map index, the ionospheric disturbances after and during the 17–23 December 2015 intense geomagnetic storm and the 2015 Saint Patrick magnetic storm are discussed, highlighting the disturbances in the DIX at different latitudinal ranges and under different magnetic conditions.